Implications of the U.S. Visa Reform for Highly-Skilled Mexican Migration - Elizabeth Salamanca Pacheco (Norteamérica)
High-skilled Mexican migrants have benefited from the opportunities offered by U.S. visa programs such as the Specialty Occupation visa (H-1B), the Treaty Investor visa (E-2), the EB-5 investor program, and the North American Free Trade Agreement professionals visa (TN). This essay analyzes the possible changes affecting these visas and identifies the main economic, social and political implications of these reforms. It recurs to two main approaches: the mixed-embeddedness framework and the transnational theory. The U.S. migration reform has forced some skilled-migrants to think about transnational spaces in order to reduce uncertainty.  E2 and EB-5 visa holders may diversify risks through a parallel presence of their businesses in both USA and Mexico. H1-B users may think about enhancing their research networks with the Mexican scientific and academic community. TN users may come back and transfer their knowledge back to Mexico. Overall, it is crucial the improvement of the Mexican institutional environment in order to further avoid the exit of valuable social and cognitive capital.